Competing Micro Economic Theories Of Industrial Profits: An Empirical Approach - Mark Glick; Eduardo M. Ochoa (Levy Economics Institute of Bard College, 1988)
Contrary to the impression given by most textbooks, microeconomics is not a homogeneous discipline. At least two major alternative theories exist which account for the long-run behavior of industrial prices and the between economic sectors in ways which are distinct from standard neoclassical explanations. Both Post Keynesian and Classical (Marxian/NeoRicardian) approaches to economics have developed a growing literature on microfoundations in recent years (see, e.g. Eichner, 1985; Dumenil & Levy, 1985).
Keywords: 330